Undiagnosed phaeochromocytoma masquerading as eclampsia. (19th January 2012) - Petrie, Joanne; Lockie, Christopher; Paolineli, Alex; Stevens, Michele; Smith, Mark; Mitchell, Catharine; Dubrey, Simon William
Abstract : The authors report the case of a previously well 34-year-old woman presenting with a hypertensive crises and a grand-mal seizure following elective caesarean section. Initial treatment of extreme hypertension, of a presumed eclamptic aetiology, with magnesium and labetalol was complicated by intermittent profound hypotensive episodes. This was accompanied by severe biventricular failure and fluctuating systemic vascular resistance. Abdominal ultrasound revealed a left suprarenal mass. A diagnosis of phaeochromocytoma was confirmed on abdominal CT and urinary assays. The patient was stabilised with α and β blockade, was successfully extubated and subsequently had the tumour surgically excised. The cardiac function returned to normal on echocardiography and she has made a complete recovery.